Prediksi Kandungan Kimia Mangga Arumanis selama Penyimpanan dengan Spektroskopi NIR - Sri Agustina; Y. Aris Purwanto; I Wayan Budiastra (PERTETA, 2015)
AbstractThe various internal qualities attributes of fruits and vegetables were able to be predicted nondestructively by using near infrared spectroscopy techniques. The objective of this study was to develop a calibration model for prediction of starch content, soluble solids content and water content of mango fruit by using near infrared spectroscopy and chemometric. The reflectance spectra of mango fruit were obtained in the wavelength range from 1000 nm to 2500 nm. The effects of different pre-process methodsand spectra treatments, such as smoothing 3 points (sa3), first derivative Savitzky-golay 9 points (dg1), and combination of smoothing 3 points (sa3) and first derivative Savitzky-golay 9 points (dg1) were analyzed.The prediction models were developed by partial least square regression (PLS). The results show that the correlation coefficient, standard error calibration and consistency for starch content of 0.95, 1.20% and 86.89% were achieved using pre-process of first derivatif Savitzky-golay 9 points; for soluble solid content of 0.90, 1.34oBrix and 86.24% were achieved using combination of smoothing 3 points and first derivatif Savitzky-golay 9 point and for water content of 0.78, 0.850 % and 99.74% were achieved using smoothing 3 points. This showed the capability of near infrared spectroscopy and the important role of chemometric in developing accurate models for the prediction of internal quality characteristics of mango fruit.Keywords: near infrared spectroscopy, internal quality, chemometric, mango, non destructiveAbstrakKualitas internal dari produk buah dan sayuran mampu dievaluasi dengan baik secara non destruktif menggunakan metode spektroskopi near infrared. Tujuan dari penelitian ini adalah untuk mengembangkan model kalibrasi untuk memprediksi kandungan pati, total padatan terlarut dan kadar air buah mangga selama penyimpanan menggunakan spektroskopi near infrared dan kemometrik. Spektra reflektan buah mangga diukur pada panjang gelombang 1000 nm sampai 2500 nm. Pengaruh metode pra-proses data yaitu penghalusan 3 titik, turunan pertama Savitzky-golay 9 titik, serta kombinasi penghalusan 3 titik dengan turunan pertama Savitzky-golay 9 titik terhadap ketelitian model kalibrasi juga dianalisis. Model prediksi dikembangkan dengan menggunakan regresi partial least square (PLS). Model prediksi dengan spektroskopi near infrared yang dikembangkan menghasilkan koefisien korelasi, standard error calibration(SEC) dan konsistensi untuk kandungan pati adalah 0.95, 1.20%, dan 86.89% yang diperoleh dari data praproses turunan pertama Savitzky-golay 9 titik, untuk total padatan terlarut, yaitu 0.90, 1.34oBrix, dan 86.24% yang diperoleh dengan menggunakan kombinasi antara penghalusan 3 titik dan turunan pertama Savitzkygolay 9 titik, sedangkan untuk kadar air yaitu 0.78, 0.850%, dan 99.74% diperoleh dengan menggunakan penghalusan 3 titik. Dapat disimpulkan bahwa model prediksi spektroskopi near infrared untuk menduga kandungan internal dari buah mangga arumanis telah dikembangkan dengan baik.Kata kunci: spektroskopi near infrared, kualitas internal, kemometrik, mangga, non destruktifDiterima: 10 Desember 2014; Disetujui: 09 Maret 2015